The effects of wind-induced inclination on the dynamics of semi-submersible floating wind turbines in the time domain. (April 2016) - Antonutti, Raffaello; Peyrard, Christophe; Johanning, Lars; Incecik, Atilla; Ingram, David
Abstract: This study focusses on the coupling effects arising from the changes in the hydrodynamic behaviour of a semi-submersible floating wind turbine when it undergoes large inclinations under wind loading. By means of a range of time-domain simulations, it is shown that both the hull geometric nonlinearity effect and the alteration of viscous hydrodynamic forces can significantly affect the dynamics of a typical floating wind turbine operating in waves at rated conditions. The consequences of said effects for both aligned and misaligned wind and waves are explored. In general terms inclinations are found to increase motions, where the modes that are more affected depend on the relative direction between incident wind and waves. Understanding the sources of aero-hydrodynamic coupling is key to providing sound design and modelling guidelines for the coming generation of floating wind turbines. Highlights: Floating wind power requires cost-effective, and hence typically small support platforms. Wave loads on small semi-submersible floating wind turbines are sensitive to wind-induced inclination. A time-domain model allows to integrate hydrodynamic, aerodynamic, and gyroscopic forces, and observe their coupling. The effect of wave load alterations on floating wind turbine dynamics is investigated for inline and cross wind and waves. Significant 'inclination effects' are found. Experimental results uncaptured by the classic modelling approach are explained.